Share Price Reaction to Dividend Announcements and the Interaction with Earnings Announcements in the Malaysian Stock Market - Yip, Peng-Poi; Isa, Mansor; W. Kester, George; Lee, Siew-Peng (Asian Journal of Business and Accounting, 2010)
This study examines the market reactions to dividend announcements and the interaction with earnings announcements in the Malaysian stock market. Data was obtained for a sample of one thousand and eighty eight (1088) dividend announcements from firms whose shares were traded on the Malaysian stock exchange from 2004 to 2008. Abnormal returns were calculated using the market model. The results are partially consistent with the dividend information signalling hypothesis. There are positive abnormal returns related to dividend increase and dividend unchanged announcements, but insignificant for dividend decrease announcements. Combining dividend announcements with earnings announcements that take place well before dividend announcements, we find that both earnings and dividends exert their influence independently on share prices.